Exome sequencing of pashtun familial epilepsy in Pakistan reveals novel variants in LAMA5, KCNQ2 and GNAO1 - Qaisar Ali; Sadiq Azam; Jamila Javed; Muhammad Zaheer; Saqib Ullah; Aqib Iqbal; Ibrar Khan; Shoaib Ur Rehman (Molecular Biology Reports, 2026)

Neuroprotective effect of Continentalic acid by targeting NF-κB/Bcl-2 and oxidative stress signaling in traumatic brain injury in male BALB/c mice - Sana Zafar; Maryam Jamil; Muhammad Ibrar Khan; Ashraf Ullah Khan; Kifayat Ullah Shah; Eun Kyoung Seo; Salman Khan (Molecular Biology Reports, 2026)

Comparative Chloroplast Genomics of Sugar Beet and Wild Relatives: Insights into Photosystem Gene Regulation and Stress Tolerance - Muhammad Sameeullah; Abdullah; Neelam Batool; Ibrar Ahmed; Mehmet Cengiz Baloglu; Noreen Aslam; Mehmet Örgeç; Ekrem Gurel; Mohammad Tahir Waheed; Songul Gurel (Functional & Integrative Genomics, 2026)

Zircon and apatite geochemical and isotopic constraints on magma fertility and magmatic evolution of porphyry CuAu mineralization at the Ting Darigun prospect, Chagai Belt, Western Pakistan - Muhammad Hafeez; Xiaoyong Yang; Ahmed Shah; Zahra Abbasi; Salman Ahmed Khattak; Ibrar Khan (Lithos, 2026)

Climate filtering of soil food webs drives divergent bottom-up and top-down regulation during grasslands recovery - Muhammad Ibrar; Meiqun Sheng; Yanbao Lei; Jie Shen; Xianzhi Deng; Juan Xue; Lin Liu; Igor Bogunovic; Geng Sun (Agriculture, Ecosystems & Environment, 2026)

Artificial intelligence-driven metallogenic typing of pyrite from global ore systems - Muhammad Amar Gul; Asia Kanwal; Mohamed Faisal; Tehseen Zafar; Rizwan Sarwar Awan; Shamim Akhtar; Ibrar Khan; Xiaoyong Yang (Journal of Geochemical Exploration, 2026)

FlgE–TLR5 interaction and its association with immune and microbiota responses in Asian swamp eel fed Bacillus velezensis - Nourhan Nassar; Ibrar Muhammad Khan; Samiullah Khan; Abdul Qadeer; Ni Du; Zaigui Wang (Fish & Shellfish Immunology, 2026)

The rising power of females: Dioecious shrub enhances soil organic carbon sequestration via fungal necromass in chronosequence of desertified alpine grassland restoration - Dongming Chen; Muhammad Ibrar; Fei Yan; Geng Sun; Ran Xue; Aomei Jia; Jiqiong Zhou; Yongheng Gao; Congyu Ma; Meng Wang; Jian Zhang; Zhouwen Ma; et al. (Journal of Environmental Management, 2026)

Tracing subduction initiation in the Neo-Tethyan Realm: Geochemical and isotopic signatures in lherzolites of the Sapat Complex, Northern Pakistan - Zaheen Ullah; Qigui Mao; Asad Khan; Meng Zhang; Dunfeng Xiang; Wang Hao; Tehseen Zafar; Wenjiao Xiao; Adnan Khan; Muhammad Ibrar (Lithos, 2026)

Improving RGB image recognition in the YOLO11n algorithm for accurate detection of tea plant diseases - Jinxian Tao; Xiaoli Li; Jingfei Zhang; Muhammad Shoaib; Muhammad Adnan Islam; Ibrar Ahmad; Yong He; Sitan Ye; Yujie Wang; Binhui Liao; Mostafa Gouda (Journal of Zhejiang University-SCIENCE B, 2026)

Genomic insights into phage SGP007 reveal a potent therapeutic candidate for targeted control of salmonellosis in poultry - Sidra Tul Muntaha; Gul Nabi Khan; Ibrar Khan; Muhammad Hassan; Iqbal Ahmed Alvi; Tawaf Ali Shah; Gehan M. Elossaily; Turki M. Dawoud (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Anti-arthritic and anti-inflammatory potential of newly synthesized 2,3-disubsituted thiazolidine-4-one derivatives in CFA-induced arthritis model by targeting TLR4/NF-κB and MAPK signaling - Muhammad Ibrar Khan; Sana Zafar; Muzaffar Abbas; Ashraf Ullah Khan; Kifayat Ullah Shah; Salman Khan (Inflammopharmacology, 2026)

Hydrothermal synthesis of novel Mn3O4-Nd2O4 nano-hybrid as bi-functional electrocatalyst for water splitting - Muhammad Ibrar; Iram Manzoor; Mostafa A. Ismail; Misbah Shareef; Habiba Batool; Sana Ben Khalifa; Saleh Chebaane; Zeineb Klai (Fuel, 2026)

Formaldehyde detoxification by the moss Racomitrium japonicum - Tiefeng Chai; Feng Lu; Xin Deng; Ningyuan Fei; Xia Hu; Hongxia Xia; Wanting Li; Ke Chen; Ying Dai; Muhammad Ibrar; Yanbao Lei (Environmental Research, 2026)

Reservoir characterization for hydrocarbon assessment of Eocene carbonates in Meyal area, Potwar Plateau, Pakistan: implications from geophysical logs data - Yasir Hamid; Muhammad Kamran; Syed Mamoon Siyar; Saqib Mehmood; Taqweem Ul Haq Ali; Fayaz Ali; Ibrar Ul Haq; Izhar Ullah; Kamran Shams; Sartaj Husain (Carbonates and Evaporites, 2026)

Retraction notice to ‘Exploring the adsorption efficacy of Cassia fistula seed carbon for Cd (II) ion removal: Comparative study of isotherm models’ [Environ. Res. 235 (2023) 116676] - Sasireka Senniappan; Shanmughaprabha Palanisamy; Vellingiri Manon Mani; Mridul Umesh; Chandramohan Govindasamy; Muhammad Ibrar Khan; Sabarathinam Shanmugam (Environmental Research, 2026)

Tectonic and metallogenic processes along the east Tethyan metallogenic domain (Lhasa-southern Tibet, Kohistan island arc and Chagai magmatic belt): a perspective review - Muhammad Hafeez; Xiaoyong Yang; Ahmed Shah; Ibrar Khan; Zahra Abbasi; Salman Ahmed Khattak; Gendenjamts Baatar (International Geology Review, 2026)

miR-34c regulates the proliferation, apoptosis, and testosterone synthesis of bovine leydig cells by targeted ATG5 gene - Tongtong Tu; Xin Wang; Shuangshuang Cui; Xiang Meng; Ibrar Muhammad Khan; Ning Song; Yunhai Zhang; Hongyu Liu (Theriogenology, 2026)

Real-time terrain classification for all-wheel drive robotic electric tractors using multi-sensor fusion and machine learning - Tamiru Tesfaye Gemechu; Jun Zhou; Guoliang Lai; Ibrar Ahmad; Luke Toroitch Rottok; Yade Li; Tabinda Naz Syed; Muhammad Aurangzaib (Journal of Terramechanics, 2026)

Metagenomic insights into phosphorus cycling after alpine grassland restoration - Hanyong Zeng; Muhammad Ibrar; Meiqun Sheng; Xianzhi Deng; Jun Zhou; Yanbao Lei; Geng Sun (Plant and Soil, 2025)

Evaluating Soil Reclamation and Growth Enhancing Potential of Various Types of Biochar with Respect To Rice Crop Cultivated in Saline Sodic Soil - Imran Shehzad; Ghulam Sarwar; Abid Mahmood; Kashf Mehmood; Zuhair Hasnain; Muhammad Zeeshan Manzoor; Danish Ibrar; Saqib Bashir; Manzer H. Siddiqui; Saud Alamri; Shahbaz Khan (Journal of Soil Science and Plant Nutrition, 2025)

Ex-situ multi-media bioleaching and functional characterization of indigenous fungal strains for chromium and zinc remediation in polluted soils - Ibrar Khan; Muhammad Bilal Akram; Aneela Rehman; Mujaddad Ur Rehman; Tawaf Ali Shah; Saad A. Alamri; Yasser S. Mostafa; Abdulrahman A. Almehizia (Biodegradation, 2025)

Synergistic effect of carbon nanotubes decorated spinel ferrites nanocomposite for robust photocatalytic degradation of persistent environmental pollutants - Sadaf Fatima; Bushra Shaheen; Norah Alomayrah; Noor ul Ain; Muhammad Ibrar; Muhammad Farooq Warsi; Imran Shakir (Journal of Water Process Engineering, 2025)

Ultraviolet assisted defects engineering of metal organic frameworks towards high performance oxygen evolution reaction - Rana Sami Ul Haq; Zhihao Lei; Shuai Qi; Muhammad Ibrar Ahmed; Vibin Perumalsamy; Yitong Cao; Kavitha Ramadass; Binodhya Wijerathne; Xun Geng; Sohail Ahmed; Long Hu; Liang Qiao; et al. (Chemical Engineering Journal, 2025)

Climate change and nutrient influx disrupt karst ecosystem dynamics and tufa deposition in Huanglong, China - Muhammad Ibrar; Bing Li; Hanyong Zeng; Anđelka Plenković-Moraj; Kazimir Miculinić; Dejun An; Yanbao Lei; Geng Sun (CATENA, 2025)

Comprehensive Molecular Profiling of AcrAB-TolC Efflux Pump Genes in Salmonella typhi Isolates from Typhoid Infected Patients - Muhammad; Sadiq Azam; Noor Rehman; Alaa S. Alhegaili; Ibrar Khan; Aakash Ahmad; Atif Ali Khan Khalil; Sajid Ali (Current Microbiology, 2025)

Nutrient limitations drive microbial carbon use efficiency and soil carbon sequestration in grassland restoration - Meiqun Sheng; Muhammad Ibrar; Yanbao Lei; Jie Shen; Xianzhi Deng; Juan Xue; Lin Liu; Geng Sun (Plant and Soil, 2025)

Microbial processes dominate DOM degradation in alpine karst lakes over photochemical effects - Qinqin You; Hanyong Zeng; Muhammad Ibrar; Dalin Zhu; Demeng Zhao; Yutao Cao; Yunde Zhang; Yanbao Lei; Geng Sun (Environmental Research, 2025)

Phthalate ester contamination in groundwater at the Himalayan-Potohar Interface: health risks in Rawalpindi, Pakistan - Hidayat Ullah; Bakht Rawan; Marwan Ullah; Muhammad Ibrar Shinwari; Thiago Machado da Silva Acioly; Patricio De los Rios-Escalante; Fedlu Kedir Sabir; Muhammad Ilyas (Environmental Monitoring and Assessment, 2025)

7β-(3-ethyl-cis-crotonoyloxy)-1α-(2-methylbutyryloxy)-3,14-dehydro-Z-notonipetranone (ECN) attenuates inflammation and oxidative stress via MAPK, and Nrf2/HO-1 signaling in Traumatic brain injury - Sana Zafar; Maryam Jamil; Muhammad Ibrar Khan; Fakhar ud Din; Eun Kyoung Seo; Salman Khan (Chemico-Biological Interactions, 2025)

Genetic determinants of heat content in chile pepper (Capsicum spp.) revealed by multi-locus genome-wide association mapping - Muhammad Ibrar Khan; Dennis N. Lozada; Amol N. Nankar; Ehtisham S. Khokhar; Seyed Shahabeddin Nourbakhsh (Euphytica, 2025)

Challenges and outlooks for the polyoxometalates, metal-organic frameworks (POMs-MOFs) hybrid materials in water treatment technologies - Ghulam Murtaza; Muhammad Ibrar Ahmed; Kewei Yu; Xingda An; Syed Shoaib Ahmad Shah; Manzar Sohail (Environmental Research, 2025)

Assessing the Influence of Potassium Fertilizer Variations on Growth, Yield, and Crop Quality of Sugarcane (Saccharum officinarum L.) Genotypes - Wajid Ali Hisbani; Bonface O. Manono; Muhammad Nawaz; Kashf Mehmood; Zuhair Hasnain; Afroz Rais; Sohail Irshad; Danish Ibrar; Manzer H. Siddiqui; Saud Alamri; Shahbaz Khan (International Journal of Plant Production, 2025)

Moringa Biopriming with Zn Spray Improved Nutrients Rich Biofortified Chickpea Grains and Drought Tolerance at Reproductive Stages Under Arid Environment - Hamid Nawaz; Malik Muhammad Yousaf; Nazim Hussain; Tanveer Hussain; Malik Waqar Yousaf; Malik Ibrar Yousaf; Mona S. Alwahibi; Mohamed S. Elshikh; Baber Ali; Rashid Iqbal (Journal of Crop Health, 2025)

Genetic Divergence Among Sorghum (Sorghum bicolor L.) Genotypes Grown Under Rainfed Conditions - Rafiq Ahmad; Ghulam Shabbir; Syed Farman Ullah; Danish Ibrar; Muhammad Ilyas; Esam M. Al-Shaebi; Yawen Zeng; Abdul Qayyum (Journal of Crop Health, 2025)

Diagenetic evolution of Early Eocene Chorgali Formation in the Upper Indus Basin of Pakistan: outcrop, petrographic and geochemical signatures - Muhammad Ibrar; Mumtaz Muhammad Shah; Maqsood Ur Rahman; Imran Ahmad (Carbonates and Evaporites, 2025)

Application of zinc nanoparticles as seed priming agent improves growth and yield of wheat seedlings grown under salinity stress by enhanced antioxidants activities and gas exchange attributes - Sara Zafar; Shahbaz Khan; Danish Ibrar; Muhammad Kamran Khan; Zuhair Hasnain; Kashf Mehmood; Afroz Rais; Safia Gul; Sohail Irshad; Muhammad Nawaz (Cereal Research Communications, 2024)

Plastics adsorption and removal by 2D ultrathin iron oxide nanodiscs: From micro to nano - Yitong Cao; C.I. Sathish; Zhixuan Li; Muhammad Ibrar Ahmed; Vibin Perumalsamy; Chaojie Cao; Chenxi Yu; Binodhya Wijerathne; Adrew Fleming; Liang Qiao; Shaobin Wang; Jiabao Yi (Chemical Engineering Journal, 2024)

Integrated Application of Micronutrients Improves Productivity and Seed Quality of Canola Crop under Conventional Tillage System - Muhammad Ijaz; Shahbaz Khan; Sami Ul-Allah; Abdul Sattar; Ahmad Sher; Muhammad Nawaz; Amjad Hussain; Afroz Rais; Safia Gul; Danish Ibrar; Manzer H. Siddiqui; Abdel-Rhman Z. Gaafar; et al. (International Journal of Plant Production, 2024)

Correction: A detailed investigation of Jutana formation for depositional setting in Indus Basin, Pakistan - Muhammad Ibrar; Hameed Ur Rehman; Suleman Khan; Syed Saddam Hussain; Maqsood Ur Rahman; Abdullah Khan (Carbonates and Evaporites, 2024)

Integrated sedimentary and diagenetic constraints for delineating the reservoir potential of Jurassic carbonate sequences in the autochthonous Samana Suk Formation, Attock-Cherat Nizampur Area, Pakistan - Muhammad Ibrar; Sajjad Khan; Mehboob Ur Rashid; George Kontakiotis; Ihtisham Islam; Hammad Tariq Janjuhah; Assimina Antonarakou (Carbonates and Evaporites, 2024)

A detailed investigation of Jutana Formation for depositional setting in Indus Basin, Pakistan - Muhammad Ibrar; Hameed Ur Rehman; Suleman Khan; Syed Saddam Hussain; Maqsood Ur Rahman; Abdullah Khan (Carbonates and Evaporites, 2024)

Identification and validation of restricted seed color polymorphic sites in Barley (Hordeum vulgare L.) using SNPs derived CAPS markers - Murad Ali; Danish Ibrar; Zuhair Hasnain; Afroz Rais; Shahbaz Khan; Kashf Mehmood; Sami Ullah; Ali Bakhsh; Safia Gul; Muhammad Musawir Khan; Waqar Khan; Muhammad Nisar; et al. (Genetic Resources and Crop Evolution, 2024)

Effect of heterogeneity on the diffusion of Pb in apatite for petrochronological applications: A multiscale approach to characterizing the influence of apatite chemistry and anisotropy on Pb diffusion - Matee Ullah; Urs Klötzli; Ce’cile Gautheron; Laurent Tassan-Got; Fakhrul Islam; Muhammad Younas; Kamran Shehzad; Muhammad Khubab; Muhammad Ibrar; Bilal Wadood (Lithos, 2023)

RETRACTED: Exploring the adsorption efficacy of Cassia fistula seed carbon for Cd (II) ion removal: Comparative study of isotherm models - Sasireka Senniappan; Shanmughaprabha Palanisamy; Vellingiri Manon Mani; Mridul Umesh; Chandramohan Govindasamy; Muhammad Ibrar Khan; Sabarathinam Shanmugam (Environmental Research, 2023)

Daidzein attenuated paclitaxel-induced neuropathic pain via the down-regulation of TRPV1/P2Y and up-regulation of Nrf2/HO-1 signaling - Sana Zafar; Yong Luo; Li Zhang; Chang Hu Li; Adnan Khan; Muhammad Ibrar Khan; Kifayatullah Shah; Eun Kyoung Seo; Feng Wang; Salman Khan (Inflammopharmacology, 2023)

Comparative valuation of the chlorpyrifos, acetamiprid, and lambda-cyhalothrin toxicity and their hematological and histopathological consequences in pigeons - Shumaila Noreen; Ibrar Muhammad Khan; Muhammad Shehzad Khan; Bibi Zarnaab; Iram Gul; Muhammad Zahoor Khan; Waqar Azeem Jadoon; Shehzad Ghayyur; Yong Liu (Environmental Science and Pollution Research, 2023)

MoS2-based lamellar membranes for mass transport applications: Challenges and opportunities - Muhammad Khurram Shahzad; Fida Hussain Memon; Faheeda Soomro; Muzaffar Iqbal; Aliya Ibrar; Ayaz Ali Memon; Jong Hwan Lim; Kyung Hyon Choi; Khalid Hussain Thebo (Journal of Environmental Chemical Engineering, 2023)

Transcriptomics for Drought Stress Mediated by Biological Processes in-relation to Key Regulated Pathways in Gossypium darwinii - Cuilian Xu; Muhammad Kashif Ilyas; Richard Odongo Magwanga; Hejun Lu; M Kashif Riaz Khan; Zhongli Zhou; Yujun Li; Zhengcheng Kuang; Asif Javaid; Danish Ibrar; Abdul Ghafoor; Kunbo Wang; et al. (Molecular Biology Reports, 2022)

Metabolic Engineering to Improve Docosahexaenoic Acid Production in Marine Protist Aurantiochytrium sp. by Disrupting 2,4-Dienoyl-CoA Reductase - Shitong Liang; Xuewei Yang; Xingyu Zhu; Muhammad Ibrar; Liangxu Liu; Siting Li; Xia Li; Tian Tian; Shuangfei Li (Frontiers in Marine Science, 2022)
Docosahexaenoic acid (DHA) has attracted attention from researchers because of its pharmacological and nutritional importance. Currently, DHA production costs are high due to fermentation inefficiency; however, improving DHA yield by metabolic engineering in thraustochytrids is one approach to reduce these costs. In this study, a high-yielding (53.97% of total fatty acids) DHA production strain was constructed by disrupting polyunsaturated fatty acid beta-oxidation via knockout of the 2,4-dienyl-CoA reductase (DECR) gene (KO strain) in Aurantiochytrium sp. Slight differences in cell growth was observed in the wild-type and transformants (OE and KO), with cell concentrations in stationary of 2.65×10 6 , 2.36×10 6 and 2.56×10 6 cells mL -1 respectively. Impressively, the KO strain yielded 21.62% more neutral lipids and 57.34% greater DHA production; moreover, the opposite was observed when overexpressing DECR (OE strain), with significant decreases of 30.49% and 64.61%, respectively. Furthermore, the KO strain showed a prolonged DHA production period with a sustainable increase from 63 to 90 h (170.03 to 203.27 mg g −1 DCW), while that of the wildtype strain decreased significantly from 150.58 to 140.10 mg g −1 DCW. This new approach provides an advanced proxy for the construction of sustainable DHA production strains for industrial purposes and deepens our understanding of the metabolic pathways of Aurantiochytrium sp.

Biosurfactants and chemotaxis interplay in microbial consortium-based hydrocarbons degradation - Muhammad Ibrar; Salman Khan; Fariha Hasan; Xuewei Yang (Environmental Science and Pollution Research, 2022)

Melatonin Rescue Oxidative Stress-Mediated Neuroinflammation/ Neurodegeneration and Memory Impairment in Scopolamine-Induced Amnesia Mice Model - Tahir Muhammad; Tahir Ali; Muhammad Ikram; Amjad Khan; Sayed Ibrar Alam; Myeong Ok Kim (Journal of Neuroimmune Pharmacology, 2019)

Chaetomium endophytes: a repository of pharmacologically active metabolites - Nighat Fatima; Syed Aun Muhammad; Ibrar Khan; Muneer Ahmed Qazi; Irum Shahzadi; Amara Mumtaz; Muhammad Ali Hashmi; Abida Kalsoom Khan; Tariq Ismail (Acta Physiologiae Plantarum, 2016)